Low pressure injection molding of boron admixed 316l stainless steel for engineering applications - Aslam, M. (Asian Research Publishing Network, 2016)
This study was conducted to evaluate the effects of elemental boron on densification of 316L stainless steels. Elemental nano size boron (nB) powder of 0.5, 1 and 1.5 wt. was blended with 316L SS to produce homogeneous feedstock for low pressure powder injection molding (LPIM) process. LPIM molded samples were sintered at 1230Â°C using high vacuum 10-5Torr. The Results showed that addition of elemental boron has favorable effects on densification. Addition of 0.5 wt nano size elemental boron in 316L SS has enhanced densification up to 98.5. Defect free gears were injection molded and sintered successfully using optimal sintering cycle. Â©2006-2016 Asian Research Publishing Network (ARPN).